2016
DOI: 10.1093/scan/nsw116
|View full text |Cite
|
Sign up to set email alerts
|

The µ-opioid system promotes visual attention to faces and eyes

Abstract: Paying attention to others' faces and eyes is a cornerstone of human social behavior. The µ-opioid receptor (MOR) system, central to social reward-processing in rodents and primates, has been proposed to mediate the capacity for affiliative reward in humans. We assessed the role of the human MOR system in visual exploration of faces and eyes of conspecifics. Thirty healthy males received a novel, bidirectional battery of psychopharmacological treatment (an MOR agonist, a non-selective opioid antagonist, or pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 63 publications
6
38
1
Order By: Relevance
“…However, the doses used by Zacny and Lichtor were three to six times the amount administered in this study. A previous study from our lab reported no significant changes in subjective state in healthy participants using a 10mg per oral dose of morphine (Chelnokova et al, 2016;Eikemo et al, 2016;Hanks et al, 1995).…”
Section: Control Measuresmentioning
confidence: 57%
See 4 more Smart Citations
“…However, the doses used by Zacny and Lichtor were three to six times the amount administered in this study. A previous study from our lab reported no significant changes in subjective state in healthy participants using a 10mg per oral dose of morphine (Chelnokova et al, 2016;Eikemo et al, 2016;Hanks et al, 1995).…”
Section: Control Measuresmentioning
confidence: 57%
“…Participants then received either 10 mg morphine or placebo (double-blind) and were told to swallow the pills immediately with water, and to not look at the pills while ingesting. As in a previous pharmacological study conducted in our lab (Chelnokova et al, 2014;Chelnokova et al, 2016;Eikemo et al, 2016) participants were told that the pills could be either morphine, placebo or naltrexone. Although naltrexone was not included in the present design, the information was kept to avoid recruitment of participants attracted specifically by the prospect of morphine treatment.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations